Микрокалориметрическое исследование гидратации полинуклеотидов поли(dА)·поли(dТ) и поли(dG)·поли(dС) - Мревлишвили, Г.М.; Сохадзе, В.М.; Джапаридзе, Г.Ш.; Татишвили, Д.А.; Якобашвили, Н.Э. (Биополимеры и клетка, 1989)
Определена гидратация поли (dА) • поли(dТ) и поли(dG) • поли(dС) в растворах и гелях при различном содержании воды. Показано, что для поли (dА), поли (dТ) она не меняется во всем изученном интервале относительной влажности, составляя 27,0 ± 1 М Н₂O/МПO. Гидратация поли(dО) • поли(dС) при высоком влагосодержании составляет 16,0 М Н₂O/МПO и уменьшается до 12,0 М Н₂O/МПO при высоких концентрациях полимера. Визначено гідратацію полі (dА) · полі (dТ) та полі (dG) · полі (dС) у розчинах і гелях за різного вмісту води. Показано, що для полі (dА), полі (dТ) вона не змінюється в усьому вивченому інтервалі відносної вологості, складаючи 27,0 ± 1 М Н₂O/МПO. Гідратація полі(dG) · полі(dС) за високого вмісту вологи становить 16,0 М Н₂O/МПO і зменшується до 12,0 М Н₂O/МПO за високих концентрацій полімеру. The calorimetric data show: 1) poly (dA) •poly (dT) hydration is nat = 27.0 ± l M H₂O/MBP at all values of relative humidity (RH); 2) poly (dG) • poly (dC) hydration at high values of RH is nGC = 16.0 ± 1 MH₂O/MBP; 3) thermodynamic parameters of ice-water phasetransition in poly(dQ) poly (dC) solutions and gels are abruptly changed with a decrease of the total water content (in the RH range of 90–60 %; 4) poly(dG) • poly(dC) hyd-ration at low RH is /toe = 12.0 ± 1MH₂O/MBP; 5) the observed hydration change of poly (dG) poly (dC) (by 4±1MH₂O/MBP) points to the conformational transition of this polymer within the limits of double-stranded state during the dehydration.